AN ANALYSIS OF TYPES OF ONOMATOPOEIA IN “ONE-PIECE” MANGA - Dinata, I Putu Indra; Juniartha, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research is an analysis of the types of onomatopoeia in